Hybrid Resolution Method for Efficient Depletion Analyses using Explicit Geometry Multigroup Monte Carlo - Kim Inhyung; Lujan Vidor H.; Painter Bailey; Kotlyar Dan; Fratoni Massimiliano (EPJ Web of Conferences)
The hybrid resolution (HR) method is a recently developed calculational algorithm tailored for efficient nuclear reactor analysis by leveraging multigroup (MG) Monte Carlo (MC) coupled with continuous energy MC calculations. While the HR method has demonstrated promising results in various scenarios, an anticipated challenge arises from inconsistencies of MG MC results caused by spatial homogenization when relatively coarse mesh is adopted, particularly in heterogeneous problems characterized by a strong flux gradient. To address this issue, the HR method incorporates MG MC calculations on the same explicit geometry used in continuous energy MC calculations. In other words, this approach preserves accuracy in geometry handling while solely simplifying energy treatment. In our investigation, a 3-dimensional BWR-type fuel assembly was focused on for a comparative study regarding the different geometry treatments in MG MC calculations. Various reactor parameters such as k-effective, power, flux, and atomic densities were estimated, and numerical performance was also compared in terms of the computing time and figure-of-merits. Our evaluation revealed that the explicit geometry-based HR method yielded more consistent and reliable parameters compared to the simplified coarse mesh-based scheme, reducing errors in power and flux distributions by about 10%.